5-Phenyl- and 5, 10-diphenyltetrabenzoporphyrins: Novel synthetic approach, physicochemical study with an emphasis on NMR spectroscopy, and identification of benzylated derivatives. (April 2020) - Kalashnikov, Valery V.; Chernyak, Alexander V.; Kalashnikova, Irina P.; Pushkarev, Victor E.; Tomilova, Larisa G.
Abstract: Novel synthetic approach to low-symmetry meso -phenylsubstituted tetrabenzoporphyrins (TPBs) by Zn(OAc)2 templated assembly of phthalonitrile in the presence of benzyltriphenylphosphonium chloride has been proposed affording two main products: 5-phenyl-21 H, 23 H -TBP (1) and 5, 10-diphenyl-21 H, 23 H -TBP (2) with higher yield for compound 1 . Procedure for isolation of 1 and 2 in individual high purity state has been developed supplemented with selection of an appropriate NMR solvent system (CDCl3 with 1% additive of CF3 COOH) that allowed full signal assignment in 1 Н and 13 С spectra to be made utilizing homonuclear 1 H– 1 H (COSY, NOESY, TOCSY) and heteronuclear 1 H– 13 C (HSQC) correlation techniques. Isolation and physicochemical study of a mixture of monobenzylated co-products 1a−g were carried out as well involving 1D and 2D NMR spectroscopies, which for the first time allowed not only to find out their structure, but also to determine the ratio of the positional isomers formed. Graphical abstract: Image 1 Highlights: A novel approach provides the template assembly of low-symmetry  meso -aryl-substituted tetrabenzoporphyrins (TBPs). The proposed approach first employs benzyltriphenylphosphonium salt as a meso -carbon donor. High-purity 5-phenyl- and 5, 10-diphenylTBP ligands were produced and characterized by 1 H and 13 C NMR. The so-called "benzyl adducts" were first isolated and assigned by NMR as the products of TBP core benzylation. The UV–Vis spectra of benzylated and non-benzylated TBPs do not coincide as was previously believed.